Risk estimates for children and pregnant women exposed to mercury-contaminated Oreochromis niloticus and Lates niloticus in Lake Albert Uganda - Tamale, Andrew; Ejobi, Francis; Muyanja, Charles; Naigaga, Irene; Nakavuma, Jesca; Ocaido, Micheal; Kato, Drago; Sente, Celsus; Amulen, Deborah; Rumbeiha, Wilson (Cogent Food & Agriculture, 2016)
Exposure to mercury contaminated fish predisposes populations particularly children and pregnant women to various health hazards including neurotoxicity, reproductive abnormalities and cognitive disorders. Earlier studies in the Lake Albert community have demonstrated the presence of mercury in Nile tilapia and Nile perch. However, the risk estimates for vulnerable groups such as Children and pregnant women is not well documented. Secondary data-set from previous studies were employed comprising family household size and fish consumption history, fish consumption quantity and frequency and mercury levels in fish species in comparison with FAO/WHO guidelines. Data collected was used to establish the hazard quotients (HQs) for the vulnerable group and the general population. A risk model was developed using iRISK to demonstrate the Disability Adjusted Life Years (DALYs) for eating different parts of the fish (muscle and bellyfat). HQ values (HQ = 2.05) above one for the vulnerable group were realized especially with Nile perch muscle. The highest DALYs (0.111) was obtained with tilapia muscle consumption. The study outcome reveals that vulnerable populations are at risk of non-carcinogenic complications. Therefore, there is a need for sensitization of the community especially the vulnerable groups about risks associated with consuming mercury-contaminated fish.
Keywords: Ecology; Environment Studies; Environment & Agriculture